Every Cloud Has a Silver Lining: The Role of Study Time and Class Recordings on University Students' Performance during COVID-19 - Chiara Binelli; Simona Lorena Comi; Elena Meschi; Laura Pagani (Institute of Labor Economics (IZA), 2024)
We study the impact of the COVID-19 pandemic and its side effects on the academic achievement of students in a large university located in a northern Italian region severely affected by the pandemic. Thanks to the richness of our data, we can investigate for the first time the role of two specific channels: the increase in study time due to the exceptionally strict confinement measures adopted and the availability of class recordings. We use administrative data on four cohorts of students merged with original survey data. We adopt a fixed-effect difference-in-differences approach, where we compare the outcomes of students from different enrolment cohorts observed in the same semester of their academic career before and after the COVID-19 outbreak. We find a generalized positive effect of the COVID-19 pandemic on students' academic achievement in terms of both earned credits and GPA. We provide evidence that both increased study time and the availability of class recordings contributed to mediating this positive effect.
Keywords: I23; I24; 330; COVID-19; university education; distance learning; study time